Foreign operation mode flexibility: tradeoffs and managerial responses. Issue 2 (4th May 2021) - Petersen, Bent; Benito, Gabriel R. G.; Welch, Lawrence S.
Abstract: Firms' ability to change foreign operation modes appears highly desirable in an increasingly volatile and unpredictable global environment. We propose and discuss mode flexibility as a management capability, with the aim at curbing the potential downsides of flexibility; in particular, the extra costs of coordination and contracting as well as revenue losses due to diminished partner commitment. We model the balancing and shifting of essential tradeoffs in relation to the two dimensions of mode flexibility – multiplicity and switchability – and highlight modularization and reciprocal use of real options as examples of tradeoff-shifting mechanisms that may improve the cost-benefit balance of mode flexibility.